A Comparative Study of Teaching Styles and Student Learning Responses in Two Malaysian Kindergartens - Gea, Ananda Putri Siswanto; Mavianti, Mavianti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the dynamics of teachers’ teaching styles and students’ learning responses in two preschools in Malaysia that implement different learning approaches. Kindergarten A adopts an authoritative–assertive teaching style emphasizing structure, discipline, and consistent classroom routines, while Tadika B applies a permissive–creative style that promotes freedom of expression and play-based learning. The study employs a qualitative case study approach involving four preschool teachers (two from each kindergarten) and observations of a total of 48 students (24 students in each kindergarten). Data were collected through classroom observations, in-depth interviews with teachers, and documentation analysis. The findings show that the authoritative–assertive approach in Kindergarten A fosters disciplined, organized, and instruction-responsive students who demonstrate higher levels of independence. In contrast, the permissive–creative style in Tadika B stimulates creativity, confidence, and self-expression but presents challenges in classroom management, particularly in maintaining discipline, lining up, and turn-taking. The study concludes that teaching style differences directly shape students’ learning responses, behavioral patterns, and socio-emotional development. These results highlight the need for a balanced approach that integrates both assertiveness and flexibility to create an optimal preschool learning environment. The findings offer practical implications for teachers, preschool administrators, and policymakers in designing developmentally appropriate instructional and classroom management strategies for early childhood education.